2017
DOI: 10.1002/ecy.1995
|View full text |Cite
|
Sign up to set email alerts
|

Macroevolutionary constraints to tolerance: trade‐offs with drought tolerance and phenology, but not resistance

Abstract: Plant tolerance of herbivory, i.e., the ability to recover after damage, is an important component of how plants cope with herbivores. Tolerance has long been hypothesized to be constrained evolutionarily by plant resistance to herbivores, traits that allow plants to cope with stressful growing conditions, and traits that influence the timing of damage in relation to reproduction. Variation in tolerance and resistance can be caused by differences in the identity of the plant (e.g., genotype, species, clade) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 89 publications
2
17
0
Order By: Relevance
“…Our results addressing the effects of maize domestication and spread on defense strategy evolution were consistent with theoretical predictions concerning resistance and tolerance evolution in the contexts of plant productivity-resistance trade-offs and plant resistance-tolerance trade-offs, respectively (Agrawal et al, 2010;Pearse et al, 2017;Zust and Agrawal, 2017).…”
Section: Disarmed By Agricultural Intensification: Maize Traded Westesupporting
confidence: 88%
“…Our results addressing the effects of maize domestication and spread on defense strategy evolution were consistent with theoretical predictions concerning resistance and tolerance evolution in the contexts of plant productivity-resistance trade-offs and plant resistance-tolerance trade-offs, respectively (Agrawal et al, 2010;Pearse et al, 2017;Zust and Agrawal, 2017).…”
Section: Disarmed By Agricultural Intensification: Maize Traded Westesupporting
confidence: 88%
“…Our results addressing the effects of maize domestication and spread on defense strategy evolution were consistent with theoretical predictions concerning resistance and tolerance evolution in the contexts of plant productivity-resistance trade-offs and plant resistance-tolerance trade-offs, respectively (Agrawal et al, 2010;Pearse et al, 2017;Zust and Agrawal, 2017). Namely, our results showed that resistance to WCR decreased with both maize domestication and spread, and tolerance increased as resistance decreased, as expected.…”
Section: Disarmed By Agricultural Intensification: Maize Traded Westesupporting
confidence: 91%
“…In this Special Feature, Pearse et al. () estimated tolerance to folivory, tolerance to “browsing” (through clipping), and resistance to two lepidopteran herbivores for a number of species in the Streptanthus clade. Using phylogenetically informed analyses, they found that tolerance was not constrained by phylogeny.…”
Section: New Avenues For Understanding Tolerancementioning
confidence: 99%
“…The ecological context is known to affect the magnitude and even the direction of plant tolerance (Abrams 1987, Chamberlain et al 2014, Garcia and Eubanks 2019, Pearse et al 2017, Poveda et al 2018. As an example, the indirect positive effects of herbivores on plant performance are mediated by improved soil nutrient pools or by the removal of competitors (de Mazancourt et al 2001).…”
Section: Tolerance Is Influenced By Abiotic and Biotic Factorsmentioning
confidence: 99%
See 1 more Smart Citation